Land Policy and Administration as a Basis for the Sustainable Development of the Brazilian Amazon - Childress, Malcom D (World Bank, Washington, DC, 2012)
There is enough land in the Amazon region to satisfy Brazilian society's demands for economic development, environmental management of a resource base of global importance and the challenges of agrarian reform. Yet Brazil has been unable to create a fully coherent and manageable land policy and administration system for the region which permits sustainable development goals to be achieved while reconciling special interests and uses. Instead, resource waste, private appropriation of the public domain and social conflict characterize land relations in the region. As the region becomes increasingly accessible for a variety of economic activities, and more central to Brazil's economy, the resolution of the land questions looms large as a foundational element for reconciling and ordering economic development, resource management and social priorities. Conclusion: the technical requirements to support land regularization are of a manageable scale and would require a complete geo-referencing of each parcel of land in the region, matched one-to-one with the property's entry in the land registry (cartorio).